2004
DOI: 10.1016/j.icesjms.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Do visual transects provide true population density estimates for deepwater fish?

Abstract: This study assesses the impact species ecology, fish reactions, and natural behaviour have on visual strip transect counts of deepwater fish carried out with an ROV (remotely operated vehicle). Two terraces and one canyon were visited on the continental slope of the Bay of Biscay. Species such as rabbit fish (Chimaeridae) and North Atlantic codling (Lepidion eques) appear to have avoided the ROV. The vertical distance off the bottom provided evidence that some individuals, in particular slickheads (Alepocephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 9 publications
2
78
1
Order By: Relevance
“…This was interpreted as a proxy for rhythmic increases and decreases in the swimming activity of the local zoarcid population in relation to alternately increasing and decreasing cycles of water flow. Previous studies have already demonstrated that eelpouts can adjust their behavior to match conditions of differing current strengths and directions (reviewed by Uiblein et al 2002, Trenkel et al 2004, Lorance & Trenkel 2006. Cummings and Morgan (2001) also described a strengthening of swimming rhythms during spring tidal phases for Zoarcids in the laboratory.…”
Section: Discussionmentioning
confidence: 97%
“…This was interpreted as a proxy for rhythmic increases and decreases in the swimming activity of the local zoarcid population in relation to alternately increasing and decreasing cycles of water flow. Previous studies have already demonstrated that eelpouts can adjust their behavior to match conditions of differing current strengths and directions (reviewed by Uiblein et al 2002, Trenkel et al 2004, Lorance & Trenkel 2006. Cummings and Morgan (2001) also described a strengthening of swimming rhythms during spring tidal phases for Zoarcids in the laboratory.…”
Section: Discussionmentioning
confidence: 97%
“…The survey design consisted of perpendicular transect strips (nominal lengths: 300 m along depth gradients and 60 m across) arranged in 6 (7 at Meriadzek Terrace) segments of roughly equal length, with total lengths of 24 (Meriadzek Terrace), 20 (St Nazaire Terrace) and 20 km (Belle Ile Canyon). Further details on sampling design can be found in Trenkel et al (2004). Strip transect width was calibrated to 5 m, at a distance of 1.5 m ahead of the ROV, by keeping all survey parameters constant (0.8 m above ground, fixed camera settings).…”
Section: Methodsmentioning
confidence: 99%
“…There are some topographic, hydrological and fishing intensity differences between these sites (see Trenkel et al 2004), but we do not believe that this had any effect on our analysis. The relative catchabilities were similar on both terraces and no clear difference was seen between sites in terms of the selected explanatory variables, apart from some differences in population densities.…”
Section: Suitability Of Rov Observationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, distinct responses to the approaching vehicle were identified which needed to be analyzed in detail so to be able to distinguish natural behavior from responses to anthropogenic disturbance. That underwater vehicles have a disturbance effect on fish behavior has also important consequences for fish density calculations from in situ transects, as the data may not reflect natural conditions when disturbance responses are intense and/or occur frequently (Trenkel et al 2004b, Stone et al 2008. Disturbance responses in deep-sea fishes may be caused by a number of factors like noise produced by motors and thrusters, light used for illumination purposes, motion, electromagnetic fields, or odor plumes deriving from the vehicle.…”
Section: Introductionmentioning
confidence: 99%